A novel DC-DC multilevel SEPIC converter for PEMFC systems. (28th December 2016) - Rosas-Caro, Julio Cesar; Sanchez, Victor M.; Vazquez-Bautista, Rene Fabian; Morales-Mendoza, Luis Javier; Mayo-Maldonado, Jonathan Carlos; Garcia-Vite, Pedro Martin; Barbosa, Romeli
Abstract: Electrical power processing is an essential sub-system of Proton exchange membrane fuel cell PEMFC systems, it is usually composed by a dc-dc converter for customizing the electrical energy before feeding the load, the Single-Ended Primary-Inductor Converter or simply SEPIC, is one of the converters with continuous input current, and it has been applied to a variety of industrial applications. This work explores the capability of the traditional dc-dc SEPIC to achieve high voltage gain by combining the converter with a diode-capacitor voltage multiplier and their applications to PEMFC systems. The continuous input current and high voltage gain is adequate for the power conditioning in fuel cell systems. For the discussed application, the voltage gain is regulated by PWM and may be extended by increasing the diode-capacitor multiplier structure. Main characteristics of the converter are: continuous input current, high-voltage gain, avoiding the use of extreme duty cycles and transformers, low voltage stresses in the power switches, besides the converter topology only employs a switch controlled and two inductors which allows a relatively simple implementation. Simulation and experimental results are provided to verify the theoretical analysis and proof of the operating principle for the dc-dc power converter proposed. Highlights: A novel dc-dc multilevel SEPIC converter is proposed. The converter proposed is designed to power conditioning of a PEMFC. The converter proposed operates in continuous conduction mode which allows a non-pulsed current drawn from Fuel Cell. The output voltage in the multilevel SEPIC converter can be increased by a diode-capacitor voltage multiplier. The voltage gain in the Multilevel SEPIC converter can be increased without increasing the number of inductors and employing one transistor.